2010
DOI: 10.1016/j.tpb.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model for genetic hitchhiking in the evolution of antimalarial drug resistance

Abstract: We analytically study a deterministic model for the spread of drug resistance among human malaria parasites. The model incorporates all major characteristics of the complex malaria-transmission cycle and accounts for the fact that only a fraction α of infected hosts receive drug treatment. Furthermore, the model incorporates that hosts can be co-infected. The number m of parasites co-infecting a host is either a constant or, more generally, follows a given frequency distribution. Although the model is formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 43 publications
(61 reference statements)
0
63
0
2
Order By: Relevance
“…As well, the proportion of multiple infections differs among geographical locations, and therefore the level of inbreeding differs. Previous theoretical work has reported the effect of hitchhiking and partial selfing on genetic variation (37), modeled the hitchhiking effect of drug-resistant alleles, and demonstrated that selection and recombination cannot be decoupled in the malaria life cycle (27). Although the observed level of linkage disequilibrium in the Senegal population is very low (4), the next step in the modeling will be to allow for the possibility of mixed infections in a multilocus model to examine the relation between transmission intensity and linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, the proportion of multiple infections differs among geographical locations, and therefore the level of inbreeding differs. Previous theoretical work has reported the effect of hitchhiking and partial selfing on genetic variation (37), modeled the hitchhiking effect of drug-resistant alleles, and demonstrated that selection and recombination cannot be decoupled in the malaria life cycle (27). Although the observed level of linkage disequilibrium in the Senegal population is very low (4), the next step in the modeling will be to allow for the possibility of mixed infections in a multilocus model to examine the relation between transmission intensity and linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Their results highlight the importance of studying the effect of various reproductive mechanisms on basic evolutionary outcomes. Although there has been research on the evolution of drug resistance in malaria parasites, in both mathematical models and computational simulations (24)(25)(26)(27), it has not been ascertained whether the underlying processes of random genetic drift, natural selection, and their interactions yield outcomes in the malaria life cycle that are congruent with those of the WF model.…”
Section: Significancementioning
confidence: 99%
“…Recently, Schneider and Kim (2010) introduced an analytical feasible model for the spread of antimalarial-drug resistance, which allows to study genetic hitchhiking. The model covers the important characteristics of the transmission cycle, incorporates host heterogeneity, i.e., different classes of treated and untreated hosts, and accounts for the fact that hosts can be infected by differently many parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the model allows simple conditions for the spread of resistance and its speed in terms of the fitness parameters and α . Hence, it is useful to find ‘optimal’ treatment strategies to prevent or slow down the spread of resistance (for more discussion see Schneider and Kim 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation